Implementation Regulation of the Minister of Labour No. 4 of 2022 Concerning Procedures and Requirements for Payment of Old Age Security Benefits: Implementasi Permenaker No. 4 Tahun 2022 Tentang Tata Cara dan Persyaratan Pembayaran Manfaat Jaminan Hari Tua - Shafira, Nadia (Universitas Muhammadiyah Sidoarjo, 2025)
The Old Age Security (JHT) Program is a government program that aims to fulfill workers' rights to decent work, including income, benefits, and social security. On April 26, 2022, the Minister of Manpower issued Permenaker Number 4 of 2022 which revised the previous the old age security regulations. This study aims to analysis the implementation of the Permenaker by evaluating previous cases, so that the government can learn and implement this policy more effectively. This study uses a qualitative approach with a literature review method, collecting data through literature studies. The results of the study indicate that Permenaker Number 4 of 2022 has the potential to be a better solution to the old age security problem than the previous period, as long as its implementation is optimal. Good implementation can be achieved by balancing the top-down and bottom-up approaches, because a tendency that is too dominant on one side can have a negative impact on the quality of policy implementation.